2017
DOI: 10.1007/s11764-017-0638-8
|View full text |Cite
|
Sign up to set email alerts
|

Examining the accessibility of high-quality physical activity behaviour change support freely available online for men with prostate cancer

Abstract: Efforts to improve physical activity information online and strategies to direct prostate cancer survivors to higher-quality websites and support services are needed to ensure safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…If the information is perceived as confusing or inadequate, this may contribute to unmet informational needs if not properly addressed. Research has suggested PCa patients may find it difficult to locate high‐quality information online, due to both their ability to search for the information and the lack of gold‐standard information being readily available. Interpersonal factors, such as their doctor's expertise, and community factors such as the availability of resources/services, may further contribute unmet informational needs.…”
Section: Resultsmentioning
confidence: 99%
“…If the information is perceived as confusing or inadequate, this may contribute to unmet informational needs if not properly addressed. Research has suggested PCa patients may find it difficult to locate high‐quality information online, due to both their ability to search for the information and the lack of gold‐standard information being readily available. Interpersonal factors, such as their doctor's expertise, and community factors such as the availability of resources/services, may further contribute unmet informational needs.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, compared with other distance-based approaches (e.g., print-materials, DVDs, telephone calls), online approaches have the capacity to provide not only high-quality content, but also highly tailored content. This, in addition to opportunities for interaction with others and tools designed to support self-management and decision-making [23] favors online delivery.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only two studies reported an explanation for designing a PA guidebook for cancer patients [14,16], with similar steps to the ones we adopted. Previous studies reported low levels of quality and accuracy of written PA information in cancer [21,22]. To prevent this possibility, we have applied a rigorous methodology that permitted us to realize a guidebook, according to the recent literature in the field and the current guidelines for PA in cancer.…”
Section: Discussionmentioning
confidence: 99%